(untitled) (Research, Society and Development, 2025)
This study addresses the prevalence of hypertension and diabetes mellitus among elderly indigenous people in the Amazon, focusing on the epidemiological and cultural challenges surrounding these chronic diseases. The research is limited to the analysis of the indigenous community of Aldeia Kainã, located in Manaquiri (AM), belonging to the Munduruku ethnic group. The overall objective was to identify the factors associated with the incidence of these diseases and to propose strategies for prevention and health promotion. The study had a qualitative and descriptive approach, carried out through an extension activity with clinical screening, educational lectures, and guidance on nutrition and physical activity. The results demonstrated a significant increase in chronic conditions, influenced by dietary changes, sedentary lifestyles, and barriers to accessing health services. It concludes that strengthening health education and respecting traditional knowledge are fundamental to reducing inequalities and promoting the overall well-being of the indigenous population.